Pembuatan Mesin Pengiris Singkong Pada Usaha Industri Rumah Tangga Dengan Kapasitas 40kg/Jam - Khairul Amri; Harfardi Harfardi; Rama Pranata; Sir Anderson (Politeknik Negeri Padang, 2022)
In this paper, the quality and quantity of sliced cassava chips are improved by design a new slicer machine. The strategy of increasing production capacity is by using an electric motor to drive a chopper blade that makes the faster cutting speed. Meanwhile, the blade is attached to affixed shaft to ensure an even cut. The machine is mainly composed of frame, the feed inlet, chopper blade, motor, v-belt and pulley as transmission part. The slicer machine operates in the following ways: a peeled cassava is pressed into the feed inlet, then the high speed rotating cutter will cut the material into slices, finally the slices drops from the outlet. A fabrication of the machine starts with 1. design technical drawings of the slicer machine using Catia V5R21, 2. manufacturing the frame, shaft, feed inlet and outlet, 3. assembly of all components such as: chopper, bearings, shaft, pulley, feed inlet, cover, motor 1,25 hp 1400 rpm and v-belts. The results of performance test of the slicer machine have actual capacity is 40 Kg/hour with a flatness of 3-4 mm.